Incidence of public and private investment in poverty in the Apurimac region - Huacac Mendoza, Reydy; Burgos Zavaleta, Fernando (mktDESCUBRE; Vol 1 No 19 (2022): Nineteenth Edition (January - June), 2022)
The purpose of this study is to analyze the incidence of public and private investment in reducing poverty in the department of Apurímac, during the time interval from 2004 to 2020. The scope of the research was descriptive and explanatory; non-experimental design of a longitudinal nature, technique applied documentary analysis, the population under analysis was represented by the census population, for the analysis and estimation of results the multiple linear regression model has been applied, the data processing has been carried out using the Eviews app. The results indicate that, to the extent that public investment in social and economic services has increased by one million soles, poverty levels have been reduced by -0.04883% and -0.03588% respectively; Likewise, as soon as the Gross Added Value of the private sector has presented an increase of one million soles, poverty has decreased by -0.000920%. It is concluded that during the study interval from 2004 to 2020, public investment and private investment have had significant implications in 90.68% in the reduction of monetary poverty rates in the department of Apurímac.